(untitled) (Research, Society and Development, 2024)
Dravet Syndrome (DS) is an early-onset epileptic encephalopathy that presents with drug-resistant seizures and neurodevelopmental delay. The therapeutic use of cannabidiol (CBD) in the face of DS convulsive patterns brings a new perspective of treatment in cases refractory to conventional therapy, with the aim of improving quality of life. In this systematic review, whose objective is to evaluate and compare the therapeutic response of DS patients to the use of cannabidiol, a careful analysis was carried out of the 9 articles published on the digital platforms PUBMED and SCIELO, between the years 2019 and 2024, about studies that relate DS to the use of CBD. Studies related to epidemiology were excluded and did not meet the inclusion criteria. The use of CBD has been shown to be effective in quantitatively and qualitatively reducing epileptic seizures, improving overall clinical impression, and controlling symptoms associated with DS. In addition, it showed efficacy and tolerability similar to those of the drugs already used, even though more adverse effects were identified than those of the common drugs. The therapeutic use of CBD in children and adults with DS is promising, with a significant reduction in the percentage of seizures and the symptomatology of the syndrome, even if when compared to the usual drugs it presents inferior results. As for the adverse effects related to use, the main difference is the association with other drugs, increasing or decreasing them.